PEMANFAATAN FILLER KAPUR CANGKANG KERANG SEBAGAI PENGGANTI FILLER ABU BATU UNTUK MENINGKATKAN DURABILITAS BETON ASPAL TERHADAP PERENDAMAN - Risma Masniari Simanjuntak; Gatto Kijo Abugau (Jurnal Rekayasa Teknik Sipil dan Lingkungan - CENTECH, 2020)
Efforts to minimize the damage to the road due to rainwater puddles can be done by alternative replacement of some of the asphalt concrete pavement forming material by replacing part or all of the standard filler in the form of rock ash with shell lime containing Ca(OH)2. With reference to the use of hydrated lime from limestone as a filler that can increase the durability of asphalt mixtures, the waste of shells processed into hydrated lime can be analogous to the same benefit. This research was conducted by Marshall testing method on asphalt mixtures using stone ash filler by replacing stone ash with shell lime filler with a variation ratio to get a comparison of Marshall values ​​and make a comparison of the decrease in these values ​​if the repeated dry wet process is tested using rainwater that has a pH 4,9 and will be done 2 times, 3 times, and 4 times immersion. From the analysis of the test results it was found that an increase in the stability value in increasing the percentage of shell lime filler and a smaller decrease in Marshall value due to repeated immersion compared to the use of rock ash.